Functional aspects of metatarsal head shape in humans, apes, and Old World monkeys. Issue 86 (September 2015) - Fernández, Peter J.; Almécija, Sergio; Patel, Biren A.; Orr, Caley M.; Tocheri, Matthew W.; Jungers, William L.
Abstract: Modern human metatarsal heads are typically described as "dorsally domed, " mediolaterally wide, and dorsally flat. Despite the apparent functional importance of these features in forefoot stability during bipedalism, the distinctiveness of this morphology has not been quantitatively evaluated within a broad comparative framework. In order to use these features to reconstruct fossil hominin locomotor behaviors with any confidence, their connection to human bipedalism should be validated through a comparative analysis of other primates with different locomotor behaviors and foot postures, including species with biomechanical demands potentially similar to those of bipedalism (e.g., terrestrial digitigrady). This study explores shape variation in the distal metatarsus among humans and other extant catarrhines using three-dimensional geometric morphometrics (3DGM). Shape differences among species in metatarsal head morphology are well captured by the first two principal components of Procrustes shape coordinates, and these two components summarize most of the variance related to "dorsal doming" and "dorsal expansion." Multivariate statistical tests reveal significant differences among clades in overall shape, and humans are reliably distinguishable from other species by aspects of shape related to a greater degree of dorsal doming. Within quadrupeds, terrestrial species also trend toward more domed metatarsal heads, but not to the extent seen in humans. Certain aspects of distal metatarsus shape are likely related to habitual dorsiflexion of the metatarsophalangeal joints, but the total morphological pattern seen in humans is distinct. These comparative results indicate that this geometric morphometric approach is useful to characterize the complexity of metatarsal head morphology and will help clarify its relationship with function in fossil primates, including early hominins.